Analysis of the performance of courier companies in selected listed counters in Malaysia / Suhaily Maizan Abdul Manaf, Nur Shafini Mohd Said and Nur Dalila Adenan - Abdul Manaf, Suhaily Maizan; Mohd Said, Nur Shafini; Adenan, Nur Dalila (Universiti Teknologi MARA, Perlis, 2022)
Over the past few years, the logistics industry has been growing exponentially since the presence of ecommerce. The development of online sales has played a vital role in increasing the number of courierservice providers across the region. It is interesting to explore the aspects that affect the success of courier firms, which can have a greater impact on the profitability of the companies. As a result, the primary objective of this study is set to examine the elements that affect the companies' profitability in the logistics industry over an eight-year period (2014-2020). There are six publicly traded companies in Malaysia's logistics industry that have been included in the sample. Considering that logistics is a critical component of the companies' competitiveness and profitability, and that logistics is one of the most profitable businesses, this study has used the Random Effects Model to analyse profitability. The variables involved in this investigation are firm size, liquidity, leverage, inflation rate, and unemployment rate. The obtained results have shown that firm size, liquidity, and leverage are the positive and significant variables, while inflation is positive but not significant towards profitability. However, the unemployment factor is negative but significant towards the profitability of the selected Malaysian courier companies. Given that an efficient planning system and managing and controlling the logistics system as the significant determinants of the profitable business operations, the findings provide guidance for boosting profitability and enhancing the performance of the logistics organisations